1997
DOI: 10.1111/j.1469-7793.1997.305bn.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Morphological Features of Skeletal Muscle from Mutant Mice Lacking Both Type 1 and Type 3 Ryanodine Receptors

Abstract: We generated mice with targeted disruptions in the genes for both ryanodine receptor type 1 (RyR‐1) and type 3 (RyR‐3) to study the functional roles of RyR subtypes in skeletal muscle. In permeabilized myocytes lacking both the RyRs, the Ca2+‐induced Ca2+ release (CICR) mechanism was completely lost, and caffeine failed to induce Ca2+ release. Replacement of potassium methanesulphonate in an experimental intracellular solution with choline chloride resulted in Ca2+ release in the wild‐type muscle but not in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 21 publications
3
47
0
Order By: Relevance
“…Mice lacking both RyR1 and RyR3 were also generated. These double-mutant mice did not actively move after birth and died, most probably from respiratory failure, as was the case for RyR1-deficient mice (Ikemoto et al 1997) RyRs are distributed not only in the central nervous system but also at a peripheral level. RyRs are present in the skeletal and cardiac muscle where their activation represents a crucial step for muscle contraction (Rossi and Sorrentino 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking both RyR1 and RyR3 were also generated. These double-mutant mice did not actively move after birth and died, most probably from respiratory failure, as was the case for RyR1-deficient mice (Ikemoto et al 1997) RyRs are distributed not only in the central nervous system but also at a peripheral level. RyRs are present in the skeletal and cardiac muscle where their activation represents a crucial step for muscle contraction (Rossi and Sorrentino 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The difference observed between skeletal and cardiac muscles may due to the known presence of different ryanodine recepters in the two muscles, skeletal muscle possessing RYR-1 and RYR-3 receptors, whereas cardiac muscle possesses the RYR-2 receptor. All three types of RYR receptors may contribute to the Ca mechanism in these cells, although it was reliably reported that Cl --dependent activation of Ca 2+ release occurs through the RYR-1 receptor in skeletal muscle (27). In the case of smooth muscle cells, it has been reported that RYR-2 and RYR-3 receptor genes are both present.…”
Section: +mentioning
confidence: 98%
“…In the case of smooth muscle cells, it has been reported that RYR-2 and RYR-3 receptor genes are both present. If we assume that the RYR-2 receptor does not mediate Cl --dependent Ca 2+ release in smooth muscle cells, as it is reported to do in cardiac RYR-2 (27), then the RYR-3 receptor may mediate Ca 2+ release from the SR in smooth muscle cells. As replacement of Cl -with methanesulfonate reduced the Ca 2+ -induced Ca 2+ release in the skeletal muscle of RYR-1 knock-out mice (27), both RYR-1 and RYR-3 receptors seem to be regulated by the intracellular Cl -concentration in skeletal muscle.…”
Section: +mentioning
confidence: 99%
“…These experimental conditions are expected to promote the release of all the SR Ca 2+ that is releasable by caffeine [18]. Furthermore, a solution containing 10 µM free Ca 2+ releases Ca 2+ from the SR via the CICR process in mammalian skinned muscle fibers [11,15,17,19]. Here, we found that Ca 2+ /caffeine -induced Ca 2+ release in muscle fibers from mutant mice were significantly (P < 0.001) different than that displayed by muscle fibers from controls.…”
Section: Ca 2+ /Caffeine -Induced Ca 2+ Release Is Modified In Mg29 Kmentioning
confidence: 59%
“…Others and we have previously demonstrated that under experimental conditions similar to those used here, CICR is present and functional in rabbit [15], mouse [16] and rat [11] skinned muscle fibers. Endo and Takeshima [17] have also demonstrated that CICR is present and functional in skinned skeletal myocytes from mice. These authors concluded that CICR was mediated via RyR-1 and RyR-3 in mammalian skeletal muscles, because in permeabilized myocytes lacking both the RyRs, CICR mechanism was completely lost, and caffeine failed to induce Ca 2+ release [15].…”
Section: Ca 2+ /Caffeine -Induced Ca 2+ Release Is Modified In Mg29 Kmentioning
confidence: 94%